The Design of Mass Timber Panels as Heat-Exchangers (Dynamic Insulation) - Craig, Salmaan; Halepaska, Anna; Ferguson, Katherine; Rains, Preston; Elbrecht, Jacob; Freear, Andrew; Kennedy, David; Moe, Kiel (Frontiers in Built Environment, 2021)
Mass timber products, together with careful forestry management, could help decarbonize the construction industry. These products must be long-lasting, to safely store atmospheric carbon for decades or centuries, and multi-functional, to displace materials and equipment that are emissions-intensive. This paper shows how to optimize mass timber panels as heat-exchangers, suggesting how to eliminate insulation while simplifying HVAC systems. Test panels measured the heat-exchange in steady and transient conditions, when the ventilation was driven by a fan or by thermal buoyancy. The total heat transfer was predicted accurately by theory in all cases. Further investigation is needed to understand the possible heat-recovery effects at the exterior surface.